Service Delivery: The Perceptions of Users’ of Library Services in a Private University in Africa - Kiriri, Peter N. (European Journal of Multidisciplinary Studies, 2018)
The success of a library in achieving its target in terms of vision and mission is closely linked to how its users perceive the services offered as well as their attitudes towards the same. The researcher investigates the impact the Library has on students learning through analyzing their perception and attitudes towards the services offered at the library as well as the availability of resources and the relationship of the library users with the library staff. The researcher obtained data from 254 library users, who were issued with a structured questionnaire. The findings of this study showed that postgraduate students used the library more often than their undergraduate counterparts. The study also showed that to a great extent, the library was viewed positively, and this directly affected how the library was used. Based on the findings, this paper recommended that employees undergo customer relation training to improve their relations with users, improve internet speed, and VPN connections, regularly update resources and enforce a noise control mechanism.
Keywords: Library services, Library users, Library employees, perception, Library resources, library space.